+0  
 
+6
88
1
avatar+510 

Solve for f.
 

-1 + 3f = 2f – 16

AlyssaWelligton  Mar 2, 2017
Sort: 

1+0 Answers

 #1
avatar+214 
0

-1+3f=2f-16 

Take 2f to the other side making it a negative and -1 to the other side making it a positive 

3f-2f=-16+1

f=-15 <-- Final Answer :)

 

Hope that helps

Julius  Mar 2, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details